How Do Orodispersible Tablets Behave in an In Vitro Oral Cavity Model: A Pilot Study - Neel Desai; Andrew Redfearn; Graeme MacLeod; Catherine Tuleu; Ben Hanson; Mine Orlu (Pharmaceutics, 2020)
Orodispersible tablets (ODTs) offer rapid disintegration of the dosage form when placed on the tongue, which leads to fast release of the active pharmaceutical ingredient. Despite increased use in diverse patient populations, there have been numerous challenges associated with ODTs. One such concern is the lack of standardised assessment of disintegration behaviour. In the European Pharmacopoeia, ‘orodispersibles’ are defined as such if disintegration time is faster than 3 min. Common in vitro measurement methods only provide single time point data and have limited physiological accuracy. To determine more bio-predictive disintegration kinetics, a bench-top in vitro oral cavity model (OCM) was modified and piloted to assess disintegration of three ODTs of differing hardness. All ODTs disintegrated similarly within the OCM—surface breakdown/swelling, initial ‘wash away’ and final ‘wash away’. The distinct advantage presented within this pilot study using the OCM is the opportunity to ascertain disintegration behaviour profiles of ODTs by evaluating changes in the observable area during simulated oral processing. The model could be implemented as a decision-support tool during the early stages of the drug design process to improve acceptability and further understand ODT disintegration behaviour.